PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP IMPULSIVE BUYING MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Marlina, Cici; Ulfah, Maria; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine: (1) the use of digital devices by economics lecturers at the Faculty of Education, Tanjungpura University, (2) the impulsive learning behavior of these lecturers, and (3) the impact of digital media on impulsive behavior. This study uses a quantitative approach with simple linear regression analysis. The sample of this study was 209 students of the 2018- 2021 intake of the Regular A and PPAPK Economics Education Study Programs who were selected randomly. Data collection was carried out using a Google questionnaire. The results showed that (1) 82.83% of economics students used digital devices extensively, which was included in the "very high" category; (2) 76.56% of students showed impulsive behavior, which was also included in the "very high" category. Hypothesis testing using the t-test showed that the t-count (2.524) was greater than the t-table (1.997), which confirmed the acceptance of the alternative hypothesis. The relationship value (R) was 0.088 (8.8%), which indicated a positive but low correlation. In conclusion, the use of digital devices has a positive and significant influence on impulsive buying behavior among economics students at Tanjungpura University.